Superficial CD34-positive fibroblastic tumor presenting as a retroauricular mass in an elderly male: a case report - Kupati, Shailaja; Lakkundi, Shilpa (International Journal of Research in Medical Sciences, 2026)
Superficial CD34-positive fibroblastic tumor (SCPFT) is a rare, recently recognized fibroblastic neoplasm of the skin and subcutaneous tissue, characterized by distinctive histomorphology and strong CD34 expression. It predominantly affects middle-aged and elderly individuals and typically follows an indolent clinical course. Due to its rarity and morphological overlap with other spindle cell neoplasms, accurate diagnosis can be challenging. We report a case of SCPFT in a 73-year-old male presenting with a slowly growing, painless retroauricular mass of three years’ duration. Histopathological examination revealed a well-circumscribed lesion composed of spindle and epithelioid cells with bizarre nuclei but lacking mitotic activity or necrosis. Immunohistochemistry demonstrated strong, diffuse CD34 positivity with negativity for STAT6, SOX10, β-catenin, S100, desmin, and smooth muscle actin, supporting the diagnosis of SCPFT. This case highlights the importance of recognizing SCPFT at uncommon anatomical sites and underscores the role of immunohistochemistry in differentiating it from other spindle cell tumors. Awareness of this entity is essential to ensure appropriate management and avoid overtreatment.